The influence of academic staff's personal and professional characteristics on the decision to cooperate with industry. (1st January 2014) - Franco, Mário; Haase, Heiko; Fernandes, António
University–industry cooperation is important for economic development, particularly at the regional level. Despite this relevance, there is still a lack of understanding regarding the underlying factors that drive the transfer of knowledge and technology. Therefore, this research aims to identify factors related to academic staff's personal and professional characteristics that influence the decision to cooperate with industry. To attain this objective, we built up a unique dataset of academic staff, based on a survey of the total population of a higher education institution in Portugal. Based on a logistic regression, the results reveal that variables such as gender, age and the school influence academic staff's propensity to cooperate with the business sector. We present theoretical and practical implications for academics, policy-makers and practitioners.